RANCANG BANGUN ALAT SISTEM MONITORING HIDROPONIK BERBASIS ANDROID - Micco Aureldo Micco Aureldo; Juanda Renaldi Juanda Renaldi; Riki Afriansyah Riki Afriansyah; Bangka Belitung State Manufacturing Polytechnic Yang Agita Rindri (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2025)
Indonesia is known as an agrarian country, where the agricultural sector is the backbone of the economy with a significant contribution to GDP. However, challenges such as land conversion, climate change, and environmental pollution threaten the sustainability of this sector. Hydroponics is one of the innovative solutions to deal with these problems, especially for people who have limited land. However, hydroponic methods require intensive monitoring of growth parameters such as pH, temperature, and humidity. This research develops an Arduino and ESP32-based hydroponic monitoring system integrated with an Android application using Firebase as a real-time database. The system is able to read pH, temperature, and humidity parameters, and present the data in graphical form for easy monitoring. Testing of the tool shows a high level of accuracy with a pH measurement error of 0.1% and humidity of 1.35%. This system is expected to help farmers in improving efficiency and productivity in hydroponic plant cultivation.